Byzantine empresses : women and power in Byzantium, AD 527-1204 - Garland, Lynda, 1955- (Routledge, 1999)
"Byzantine Empresses provides a series of biographical portraits of the most significant Byzantine women who ruled or shared the throne between 527 and 1204. It presents and analyses the available historical data in order to outline what these empresses did, what the sources thought they did, and what they wanted to do."--BOOK JACKET. "Lynda Garland examines the immense contribution of these women to Byzantine civilisation, which despite stereotypical criticisms in the sources based on the paradoxical combination of women and imperial power was entirely recognised and validated."--BOOK JACKET. "The well-illustrated Byzantine Empresses makes accessible the historical data of the period to provide a stimulating analysis of the contribution of Byzantine women to the empire."--Jacket